Comparison study on morphology and anatomy characteristic of paracostus bullatus (Meekiong) and paracostus eburneus (Meekiong) from Bau, Kuching Division - Noor Ain, Binti Che Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2012)
The Order Zingiberales is a monocotyledonous plant that consists of eight families with 92 genera and approximately 2111 species. The Costaceae is one of the Zingiberales members that famously known as spiral gingers or locally known as Setawar hutan due to it having spiromonostichous leave arrangement. This family recently has been revised and comprises seven genera, namely Costus, Chamaecostus, Cheilocostus, Dimerocostus, Monocostus, Paracostus and Tapeinochilos. The genus Paracostus, previously represented by only two species now has increased to six species. Among the species, P. bullatus (Meekiong) and P. eburneus (Meekiong) were the two hyper endemic species that found from Bau Limestone areas. These two species shared several characteristics and only distinguished by the floral characteristics. Therefore this project aimed to investigate details on differences on the aforementioned species via morphological and anatomical aspects. Fresh samples were collected from the type localities. The morphological and anatomical characteristic of both species were determined. Observation and measurement of fresh collections were conducted to determine morphological characteristic of both species. The result showed both species clearly differed in term of leaves colour and floral characteristic. Leaf anatomical characteristic of both species were examined by using scanning electron microscope (SEM). The types of stomata on the adaxial leaf surface of both species were similar; paracytic, hemiparacytic and anomocytic but on abaxial leaf surface the types of stomata were differed; P. bullatus had paracytic, hemiparacytic and anomocytic while P. eburneus only had anomocytic. The longest average sizes of stomata on adaxial and abaxial leaf surface belong to P. bullatus. The longest average sizes of guard cells on adaxial leaf surface belong to P. eburneus while on the abaxial leaf surface belong to P. bullatus. Trichomes were presence only on abaxial leaf surface of both species; P. bullatus and P. eburneus. Both Paracostus species clearly differed in morphological and anatomical characteristic.